Role of Alternative Dispute Resolution as a Mechanism for Administration of Justice - Renu, Shailja Chauhan (International Journal of Science and Research (IJSR), 2019)
Desire for quick and affordable justice is universal. Right to speedy trial is a right to life and personal liberty of every citizen guaranteed under Article 21 of the Constitution, which ensures just, fair and reasonable procedure. Alternative Dispute Resolution mechanisms have become more crucial for businesses operating in India as well as those doing businesses with Indian firms. There are various reasons for which ADR is preferred over the conventional way of resolving the disputes. India being a developing country, going through major economic reforms within the framework of the rule of law, for expeditious resolution of disputes and lessening the burden on the courts, alternative mechanisms for resolution (ADR) are the only alternative through arbitration, conciliation, mediation and negotiation.

Fairness in class action settlements - Piché, Catherine (McGill University, 2011)
To be made effective, class action settlements must be negotiated fairly, be perceived as fair and reasonable by the settlement parties such that they agree to their terms and substance, and be characterized as fair, reasonable and adequate by a court at the occasion of a settlement approval hearing. But how is settlement fairness defined, in a collective litigation context? By which process is the evaluation of fairness made and the approval given by the court? What role does the court correspondingly have, in that context? This thesis explores the legal policy and reasoning behind the mandatory judicial approval of class settlements, the process by which it is sought and obtained, the currently relevant factors and indicia of settlement fairness which support all decisions to approve, and the roles of the principal settlement actors, particularly the settlement judge. It suggests hypotheses for reform applicable to these approval processes, roles of the actors and standard of settlement fairness. These hypotheses are tested, for their plausibility, against empirical data obtained from the qualitative interviews of seventeen judges conducted by the author in four target jurisdictions that have similar approaches to class action settlement approvals, and where class action litigation activity is heavy: Quebec, Ontario, British Columbia, and the United States federal courts. Ultimately, the thesis proposes final recommendations for reform of the class action settlement approval procedure.
Identifier : https://escholarship.mcgill.ca/concern/theses/n009w645z
Keywords: Class action; Class action settlement; Settlement parties